2010
DOI: 10.1016/j.ijgo.2010.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of married women's beliefs about gender equity on their use of prenatal and delivery care in rural China

Abstract: Overall, women in China's rural Xinjiang and Anhui provinces do not hold strong convictions about gender equity. There was a positive correlation between belief in gender equity and use of prenatal and delivery care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…Few studies have documented awareness of human rights related to maternal health, but our results are similar to what has been found in another area of rural Bangladesh [22]. Our results are also consistent with studies carried out in China, exploring awareness of gender concepts and gender equity, closely related to human rights, which found a generally low level of awareness related to gender equity [23-25]. Building awareness of human rights and gender equity in resource-constrained settings like Bangladesh should be considered a priority for moving toward gender equality and realization of human rights as envisioned in global and national maternal health strategies [14].…”
Section: Discussionsupporting
confidence: 92%
“…Few studies have documented awareness of human rights related to maternal health, but our results are similar to what has been found in another area of rural Bangladesh [22]. Our results are also consistent with studies carried out in China, exploring awareness of gender concepts and gender equity, closely related to human rights, which found a generally low level of awareness related to gender equity [23-25]. Building awareness of human rights and gender equity in resource-constrained settings like Bangladesh should be considered a priority for moving toward gender equality and realization of human rights as envisioned in global and national maternal health strategies [14].…”
Section: Discussionsupporting
confidence: 92%
“…The National Health Services Survey data from 2008 showed that women with a college education or higher were 2.86 times more likely to give birth in a hospital than those who were illiterate (6). A study in two provinces in 2007 found that women with highschool or higher education were 3.19 times more likely to receive any professional prenatal care than those with elementary education or less (44). The relationship between higher education and contraceptive use was also shown by studies in Anhui and Shanghai (45, 46).…”
Section: Resultsmentioning
confidence: 99%
“…Several included studies showed that a low educational level (less than 6 years or illiterate) is closely related to limited knowledge about maternal health, contraceptives and warning signs of complications during pregnancy (15, 16), which, in turn, hinders poorly educated women from seeking maternal health care and using contraception (44, 46, 48). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations